Evaluation of Common Wheat Stubbles (Triticum aestivum L.) for Pulp and Paper Production - Ahmet Tutus; Mustafa Cicekler (Drvna Industrija, 2016)
The aim of the study was to determine the properties of pulp and paper produced from wheat stubble (Triticum aestivum L.), using soda-oxygen-sodium borohydride (NaBH4) cooking method. Whole wheat straw (Triticum aestivum L.) was also used for comparison with stubbles. The morphological and chemical properties of the raw materials were investigated. The results showed that stubble had high holocellulose, cellulose, and alpha-cellulose contents and low lignin content. Fiber length, fiber width, lumen diameter, and cell wall thickness were measured in order to determine suitability of the fibers for pulp and paper production. The values were used to calculate fiber parameters. The effects of these parameters on paper strength were also discussed. The effect of NaBH4 on the yield and chemical, physical, and optical properties of pulp and paper were investigated. The addition of NaBH4 increased pulp yield by 4.1 %, and improved the physical and optical properties of the pulp. The physical and optical properties of the stubble pulp were better than those of whole wheat straw pulp. It was concluded that these characteristics demonstrate the suitability of wheat stubbles for pulp and paper production.